Prospective randomized investigation implementing immunonutritional therapy using a nutritional supplement with a high blend ratio of ω-3 fatty acids during the perioperative period for head and neck carcinomas. (6th February 2018) - Hanai, Nobuhiro; Terada, Hoshino; Hirakawa, Hitoshi; Suzuki, Hidenori; Nishikawa, Daisuke; Beppu, Shintaro; Hasegawa, Yasuhisa
Abstract : Perioperative 28 days of nutritional supplementation did not affect further weight change nor changes in inflammatory markers for head and neck cancer patients with a weight loss ≥5%. Abstract: Objectives: The purpose of this study is to evaluate whether a nutritional supplement with a high blend ratio of ω-3 fatty acids can minimize weight loss and attenuate increases in inflammatory marker levels during the perioperative period in patients undergoing surgery for head and neck carcinoma. Methods: Patients with ≥5% weight loss within 6 months were considered as targets for aggressive nutritional intervention. Among these patients, those with head and neck squamous cell carcinoma, who underwent major invasive surgery with free flap reconstruction were included in the present study. The patients were randomized into two groups: the 'nutritional supplementation group' and the 'non-intervention group'. The nutritional supplementation group received two packs of Prosure® (an eicosapentaenoic acid [EPA]-enriched oral nutritional supplement) per day for 28 days during the perioperative period. Results: Compliance with the Prosure® dosage was very good at 6277/6720 ml (average) before surgery (93%) and 5229/6720 ml after surgery (78%), and a significant increase in EPA concentration was shown in the group that received Prosure® ( P < 0.0001: Welch's t -test). However, 28 days of nutritional supplementation did not lead to further weight change or changes in the inflammatory marker levels of patients were already showing cachexia (based on weight loss). Interestingly, no further change in the mean weight was noted in these patients. The incidence of postoperative complications did not differ between the two groups. Conclusion: In this trial, immunonutritional therapy using a nutritional supplement with a high blend ratio of ω-3 fatty acids from 2 weeks before surgery until 2 weeks after surgery was not effective for maintaining the nutritional status of head and neck carcinoma patients.